In vitro regeneration of Mirabilis jalapa L. (Bangladesh Journal of Scientific and Industrial Research, 2021)
In vitro regeneration of Mirabilis jalapa L., an important medicinal plant, has been successfully established from nodal explants. Maximum numbers of shoots (8.1) were obtained using Murashige and Skoog (MS) medium containing BAP (3.0 mg/l). Next to the highest response by nodal explants of M. jalapa was shown on MS medium supplemented with 2.0 mg/l BAP +1.0 mg/l IAA + 1.0 mg/l Kn. In it, the mean value of shoot number was 7.3. The highest frequency of root induction (80%) were obtained on MS medium supplemented with IAA (0.5 mg/l) and 40 ml/l coconut water. The rooted plantlets were transferred for hardening following acclimatization and finally were successfully planted in the field.Bangladesh J. Sci. Ind. Res.56(1), 25-28, 2021